TREATMENT OF SICKLE CELL ANEMIA - Dr. Salam Alkindi (Hematology, Transfusion and Cell Therapy, 2022)
Sickle cell disease (SCD) is an inherited disorder prevalent in many areas of the world including Africa, Middle East and parts of India. It is characterized by repetitive episodes of vaso- occlusive (VOC) process, leading to recurrent painful episodes, hemolytic anemia and predisposition to infection. Although VOC is a leading manifestation of SCD, and seen in about 90% of all patients with SCD, however organ specific complications such as acute chest syndrome, stroke, splenic sequestration, and many skeletal complications are also seen. Better understanding of pathophysiology of the disease as well as worldwide interest in the disease has allowed more progress on treatment and prevention of these complications and development of more focused pharmacological therapies. Hemoglobin polymerization is a primary triggering event in the pathophysiology of the disease, resulting in vascular injury and leading to the process of sickling. This usually ignite an intense inflammatory process/ tissue ischemia and increased adhesions. This understanding of the pathophysiology has allowed scientist to develop drugs (three FDA approved within the last few years), that interfere with these processes such as Voxelotor & Hydroxyurea (interfere with polymerization and enhance HbF production), L-glutamine and Omega 3 (interfere with inflammatory process and oxidative stress) and Crizanluzimab and Tinzaparin (works by inhibiting adhesion molecules). Others studies looking at similar and other pathways are ongoing, including drugs that improve adenosine triphosphate (ATP) levels and reducing 2,3-diphosphoglycerate (2,3-DPG) levels. The availability of these therapeutic interventions, will allow patients and physicians the freedom to have patient specific therapeutic interventions including development of combinations protocols. SCD is very complex and this meant that drug with multi-faceted action such as Hydroxyurea will remain with us for some time. Further progress also made in the area of bone marrow transplant (including alternative donor pool) and gene therapy /gene editing, with recently published data is very encouraging.Although the prognosis of patients with SCD has improved, due to introduction of vaccination, use of antibiotics prophylaxis and blood transfusions, however still patients are dying prematurely and further work is needed on understanding disease and its manifestation.